Nationwide dissemination of contingency management: The veterans administration initiative. (11th April 2014) - Petry, Nancy M.; DePhilippis, Dominick; Rash, Carla J.; Drapkin, Michelle; McKay, James R.
Abstract : Background: Contingency management (CM) is an empirically validated intervention but one not often applied in practice settings in the US. Objectives: The aim of this article is to describe the veterans administration (VA) nationwide implementation of CM treatment. Methods: In 2011, the VA called for integration of CM in its intensive outpatient substance abuse treatment clinics. As part of this initiative, the VA funded trainings and ongoing implementation support, and it provided direct funds for reinforcers and other intervention costs. Results: Over 100 clinics received this funding in 2011, and CM has been implemented in over 70 substance abuse treatment clinics since August 2011. Conclusions: This training and implementation experience has been highly successful and represents the largest scale training in evidence‐based treatments for substance use disorders in the VA health care system to date. Scientific Significance: This program may serve as a model for training in evidence‐based treatments. (Am J Addict 2014;23:205–210)